1983
DOI: 10.1111/j.1365-2818.1983.tb04247.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental lymphatic metastasis

Abstract: K E Y WORDS. Metastasis, neoplasm-invasion, lymphatic metastasis. S U M M A R YA model of lymphatic metastasis of cancer has been established by injecting tumour cells into the rat footpad and examining the draining popliteal lymph node. The node can probably destroy only a few tumour cells; thereafter metastasis is progressive and lethal. The tumour cells penetrate the lymphatic endothelium, in the footpad either by moving singly between intact endothelial cells, by destroying the endothelium, or by passing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Since no comparable loss is indicated for axillary and paraaortic nodes transplanted with this number of cells (Figure 4a), and it also occurs for inguinal nodes left in the primary host (Figure 4b) it is most unlikely to be an artefact. Qualitatively similar changes in the number of metastatic cells passing through the prepopliteal nodes draining the footpad of rats given 2 x 107 Walker carcinoma cells 6 days previously has also been reported (Carr & Carr, 1981). Hewitt and Blake (1975) have also shown, using the isogeneic WHT carcinoma, that the translymphnodal passage of spontaneously disseminated cells may occur.…”
Section: The Transplantation Of Metastatic Cellssupporting
confidence: 50%
See 1 more Smart Citation
“…Since no comparable loss is indicated for axillary and paraaortic nodes transplanted with this number of cells (Figure 4a), and it also occurs for inguinal nodes left in the primary host (Figure 4b) it is most unlikely to be an artefact. Qualitatively similar changes in the number of metastatic cells passing through the prepopliteal nodes draining the footpad of rats given 2 x 107 Walker carcinoma cells 6 days previously has also been reported (Carr & Carr, 1981). Hewitt and Blake (1975) have also shown, using the isogeneic WHT carcinoma, that the translymphnodal passage of spontaneously disseminated cells may occur.…”
Section: The Transplantation Of Metastatic Cellssupporting
confidence: 50%
“…As indicated by Porter et al (1973), a limiting dilution (TD50) assay would be helpful in the study of tumour metastasis but, presumably due to the previous lack of a suitable animal model (Carr & Carr, 1981;Fidler & Hart, 1982;Kim, 1984;Vandenris et al, 1985) . More importantly the method adopted was similar to a dilution assay but to avoid the need to isolate metastatic cells from a node, their numbers were assayed by determining the latency of the tumour it formed after transplantation to a fresh host.…”
mentioning
confidence: 99%
“…The dissemination of coherent masses of tumor satellites is histologically observed in tumors of epithelial origin (e.g., invasive oral carcinoma and adenocarcinoma) or melanoma [154]. In vivo, such coherent cell groups retain desmosomes and other cell-cell junctions [163], protrude into the tissue preferentially along paths of least resistance such as clefts, natural cleavage planes or tissue spaces (e.g., fiber bundles, nerves, blood vessels) [83] and can be detected in lymphatic vessels [164] and in peripheral blood [165,166]. Using time-lapse videomicroscopy, the coordinated protrusion, detachment, and migration of neoplastic cell clusters from primary tumor explants is seen upon culture in 3-D collagen lattices [99,126].…”
Section: Cellular Pattern Of Tumor Cell Migrationmentioning
confidence: 99%
“…It has been recently suggested that stromal fibroblasts and endothelial cells may acquire genetic alterations similar to those seen in tumor cells and this coevolution may provide growth and migratory advantages to both cell types (Pelham et al 2006). In vivo, migrant cell clusters retain cell-cell junctions, protrude into adjacent tissue driven by leading "pathfinder" cells, and can be detected in lymphatic vessels (Carr 1983) and in peripheral blood (Liotta et al 1976;Brandt et al 1996;Friedl and Brocker 2000). Such coordinated cell migration of neoplastic cell clusters from primary explants can also be visualized using time-lapse videomicroscopy in three-dimensional (3D) collagen matrices (Friedl et al 1995).…”
Section: Migratory Neighbors and Distant Invaders Genes And Developmentmentioning
confidence: 99%